The Perspectives of Green Economy in the Republic of Moldova under the Impact of Ecologization World Economy Megatrend - Zorina SHISHCAN; Marina KAIM (Eastern European Journal of Regional Studies, 2017)
The authors have outlined the conceptual methodology in the field as well as the relevant Strategies, Programs and Projects implemented in European Union and Republic of Moldova, and have figured out the key elements as well as the perspectives of green economy development in the country.